An Experimental Study of Stagger Angle Effect on the Performance of Marine Savonius Vertical Axis Water Turbine - Rohman, Abdul; Setiawan, Priyo Agus; Lukitadi, Projek Priyonggo Sumangun; Santoso, Emie; Ariwiyono, Nopem; Antariksih, Daisy Dwijati Kumala Ratna; So’im, Subagio; Antoko, Bambang; Permadi, Niki Veranda Agil (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
This paper investigates the performance of Savonius vertical axis water turbine by varying its stagger angles. In this study, the shape of the turbine blade is modified based on the Myring equation as well as adding a disturbance in the form of a circular cylinder placed in front of the advancing blade as a barrier. The method used in this research is an experimental study in a water tunnel at a velocity of 0.22 m/s. The turbine has size of 0.4 m in height and 0.4 m in diameter. The experiment results show that the use of a circular cylinder in front of the advancing blade has a significant effect on increasing turbine performance. This can be proven by placing a circular cylinder with , , and where the angular speed achieved is , torque coefficient and the result of maximum power coefficient is about 0.4356.